IMPLEMENTATION OF AL-QUR'AN MEMORIZATION IN IMPROVING THE QUALITY OF MEMORIZATION OF STUDENTS AT THE DARUL IKHLAS DALAN LIDANG ISLAMIC BOARDING SCHOOL - Ali Jusri Pohan; Fatimah Sahara; Lely Khairani; Riska Putri; Mar’atun Khoiriyah; Irda Auliah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to analyze the implementation of the Al-Qur'an memorization program in improving the quality of memorization of students at the Darul Ikhlas Dalan Lidang Islamic Boarding School. The study used a qualitative approach with a descriptive type. Data were collected through participatory observation, in-depth interviews, and documentation analysis involving the tahfidz supervising teacher, students in the tahfidz room, and the boarding school management. The results showed that the implementation of tahfidz was carried out in a structured manner through a combination of tasmi', ziyadah, halaqah, talaqqi, and muroja'ah methods. The tahfidz program is divided into two categories, namely special tahfidz (kamar tahfiz) with a target of 3 juz per semester and tahfidz as a subject (Qur'an Hafadz) which is mandatory for all students. The evaluation system is carried out through tasmi' before moving juz and monthly exams. Despite challenges such as differences in student abilities, consistency of memorization, and target pressure, the boarding school implemented solutions in the form of mixed halaqah coaching, intensive guidance, routine evaluation, and a controlled discipline system. This structured and consistent implementation contributes to improving the quality of students' memorization, both in terms of fluency, accuracy of tajwid, and long-term memorization resilience.